Regulatory Support for Biosequestration Projects in Australia: A Useful Model for Transition to Net-Zero Emissions? - Steven Geroe (Faculty of Law, Sriwijaya University, Indonesia, 2022)
This paper considers the effectiveness of Australian regulatory measures to support storing atmospheric carbon in plants and organic matter in soils (biosequestration), a central element of the Australian greenhouse gas (GHG) emission policy through the Emissions Reduction Fund (ERF). Eligible methodologies under the ERF are broader than those in other jurisdictions. Hence Australian experience may have international application. The functionality of Australian regulation to achieve GHG emissions reduction is considered, focusing on provisions relating to additionality, permanence, monitoring, reporting and verification of emissions bio-sequestration. This analysis is conducted by reviewing key publications by research organisations, academics, government departments, industry organisations, environmental organisations and private sector consultancies. While the integrity of Australian biosequestration offsets is generally well regarded, persistent issues have been identified with regard to the additionality of avoided deforestation methane capture in intensive agriculture and landfill gas projects. The proportion of Australian emissions represented by existing biosequestration offset projects is deficient. These issues must be addressed in order to scale up biosequestration projects as an effective element of Australia's net-zero emissions strategy. It can best be achieved by tightening Safeguard Mechanism baselines to drive demand for carbon credits and funding the Clean Energy Regulator to implement effective, independent MRV. Ongoing regulatory reform will be necessary to address such issues as they arise in the course of the implementation of specific methodologies. Nonetheless, ongoing emissions risks relating to biosequestration and other offset projects can only be adequately addressed by complementary policy to reduce emissions at the source.